Progressive-Addition Lenses for Accommodative Esotropia with a High Accomodative Element. (2nd October 2015) - Mezer, Eedy; Wygnanski-Jaffe, Tamara; Stolovich, Chaim
Abstract: Purpose : Accommodative esotropia with a high accommodative element has been typically treated with bifocal lenses. This study assessed the age-dependent efficacy of progressive-addition lenses (PAL) for a high accommodative element in improving motor and sensory performance. Methods : We evaluated PAL as an initial treatment modality or after initiating treatment with bifocals at various ages. Thirty-two patients, who did not undergo eye muscle surgery, were included in this retrospective study. Subjects were divided into 2 subgroups: 7 subjects who received PAL treatment only (median age 4.5 years), and 25 children treated with bifocals (median age 4.5 years) and then switched to PAL at the mean age of 9 years. Measurement of the deviation was performed by the alternate prism cover test. The Stereo fly test and Randot stereo test were used to assess stereoacuity. The mean follow-up periods for the subgroups were 57 and 46 months, respectively. Results : The deviation at near decreased in the PAL-only group from an average of 28 prism diopters (PD) without correction at diagnosis to zero PD with correction. Stereopsis in the PAL first group improved from an average of 113" to 54" and in the bifocals first group improved from 541" to 141". Conclusion : PAL treatment for accommodative esotropia with a high accommodative achieved good sensory and motor results. PAL and bifocals were equally beneficial as the initial treatment of young children with convergence excess esotropia.